The Evolving Role of the Oncologic Neurosurgeon: Looking Beyond Extent of Resection in the Modern Era - Bowden, Stephen G.; Han, Seunggu Jude (Frontiers in Oncology, 2018)
Neurosurgeons have played an essential role in glioma management and research for over a century. While the past twenty years have played witness to many exciting developments in glioma biology, diagnosis, and classification, relatively few novel, effective treatment strategies have been introduced. The role of neurosurgery in glioma management has been clarified, with a large body of evidence in support of maximal safe resection. However, neurosurgeons have also played a critical role in translational research during this period. The development of new MRI technologies has benefited greatly from validation with stereotactically-targeted human tissue. Careful banking of surgically acquired tissue was key to the development of a new classification scheme for glioma. Similarly, we have garnered a considerably deeper understanding of molecular and genetic properties of glioma through analysis of large surgical specimens. As our classification schemes become more sophisticated, incorporating targeted tissue sampling into the development of novel treatment strategies becomes essential. Such ex vivo analysis could be instrumental in determining mechanisms of treatment failure or success. Modern tumor neurosurgeons should consider themselves surgical neuro-oncologists, with engagement in translational research essential to furthering the field and improving outlooks for our patients.